2012
DOI: 10.1002/jctb.3698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coagulant‐flocculant reagents on aerobic granular biomass

Abstract: BACKGROUND: Technologies based on aerobic granular biomass are presented as a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…The observed connection between the process performance and AOB/NOB abundance correlates well with the results published by Val del Río et al [31], who found that a sludge retention time in excess of five days is necessary to obtain a nitrification efficiency close to 100%. In our reactors, the SRT was below six days (R1) and three days (R2) during the first 10 days of operation ( Figure S6).…”
Section: Abundance Of Aob and Nobsupporting
confidence: 90%
“…The observed connection between the process performance and AOB/NOB abundance correlates well with the results published by Val del Río et al [31], who found that a sludge retention time in excess of five days is necessary to obtain a nitrification efficiency close to 100%. In our reactors, the SRT was below six days (R1) and three days (R2) during the first 10 days of operation ( Figure S6).…”
Section: Abundance Of Aob and Nobsupporting
confidence: 90%
“…It is unknown if the presence of the polyelectrolyte added to the digested sludge to improve the centrifugation efficiency, affected the granulation process. Previous research reported that the presence of coagulant-flocculant reagents involved negative effects on the formation process and the physical properties of the aerobic granules [23]. In our study, despite the presence of polyelectrolyte the granule formation progressed acceptably as shown by (i) sludge volumetric indexes and settling velocity (just discussed above), (ii) in terms of size and biomass retention capacity ( Figure 3A).…”
Section: Experimental Procedures and Type Of Operationsupporting
confidence: 70%
“…In this sense a short feast phase is preferable to avoid filamentous outgrowth [35]. However for R1 the feast phase was longer than in RC, which promoted the growth of filamentous organism in the granules surface, while in RC this was not observed [15].…”
Section: Effects Of Operational Conditionsmentioning
confidence: 99%
“…The details about the operation could be consulted in Val del Río et al [15] for R1, Figueroa et al [16] for R2 and Val del Río et al [17] for R3.…”
Section: Reactors Operationmentioning
confidence: 99%